Quantitative Evaluation on the Drivers of PM2.5 Concentration Change in South Korea during the 1st - 3rd Seasonal PM2.5 Management Periods 1~3차 미세먼지 계절관리제 기간 중 국내 PM2.5 농도 변화 요인 분석32 - Bae, Minah; Kim, Segi; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
Since 2019, Korean Ministry of Environment has implemented the 1st - 3rd PM2.5 Seasonal Management Plans (SMP) to reduce PM2.5 concentration during high PM2.5 concentration period. In this study, we quantitatively evaluated the major drivers (meteorology, foreign emissions, and domestic emissions) of which changes led to change of PM2.5 concentrations in South Korea during the PM2.5 SMP periods (S1, Dec. 2019 - Mar. 2020; S2, Dec. 2020 - Mar. 2021; S3, Dec. 2021 - Mar. 2022) based on observational data and Community Multiscale Air Quality (CMAQ) simulation results. The nation-wide period mean PM2.5 concentration in S1, S2, and S3 decreased by 8.7, 9.1, and 10.1 μg/m3 compared to that during Dec. 2018 - Mar. 2019. Results show that anthropogenic emission reductions in Northeast Asia decreased the PM2.5 concentration by 5.9, 5.5, and 8.8 μg/m3 respectively during S1 - S3. Note that the effect of the regional emission reduction includes not only domestic emission reduction but also reductions in foreign emission impact. The combined impact of meteorology and foreign emission changes explained 65%, 61% of the total PM2.5 decreases over South Korea and the Seoul Metropolitan Area (SMA) respectively during the S1 - S3. Consequently, domestic emission reductions including governmental air quality management plans (i.e., the PM2.5 SMP) and socioeconomic changes (i.e., COVID-19 outbreak) led to PM2.5 concentration decrease in South Korea by 35% during the periods. Among seventeen provinces in South Korea, the impacts of domestic emission reduction on the PM2.5 concentration decreases were as high as 39% and 56% in the SMA and Chungnam where the major emission sources such as transportation, power generation facilities, and industrial complex locate and where the PM2.5 SMP measures were probably penetrated. It implies that the effects of domestic emission controls were meaningful to lower PM2.5 concentrations during the periods.
Keywords: Domestic emission impact; Emission impact; Meteorology impact; Pm2.5; Seasonal pm2.5 management